Training of Trainer (ToT) Tahsin Al-Qiraah With Methode Yanbu'a For TPQ Teachers in Sumbang Purwokerto District - Ismatulloh, A. M.; Waliko, Waliko (AJIRSS: Asian Journal of Innovative Research in Social Science, 2022)
The ability to read and write verses mentioned in the Qur'an is one of the main competencies that a Muslim must possess. Various methods of transmitting knowledge about reading and writing the Qur'anic verses have been developed since Islam's early development. One method that is considered able to adapt during the various eras is the Yanbu'a Method. To transmit knowledge about the Yanbu'a method, a training of trainer's activity was conducted with the subject of training for TPQ teachers in the sub-district of Sumbang. Training trainers are considered the best way to reach a wider audience and enlarge the scope of the Yanbu'a method. After intensive training and followed up by one month of mentoring, it can be concluded that the Yanbu'a method taught by the two-way learning method is likely to survive during the pandemic. Even so, the obstacles in implementing the Yanbu'a method are the transition process that requires good competence and the availability of learning materials that are not yet sustainable in the sub-district of Sumbang